Droughts and State Failure: Unwilling to Learn and Unwilling to Distribute - Rathore, M. S. (Water Nepal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mr. Rathore examines the broad drought management policies of India and coping strategies adopted by various actors since independence and identify gaps to suggest appropriate measures to mitigate or reduce the impact of drought. His paper examines the nature and intensity of drought, document perception and impacts of drought and analyse the responses and management strategies of various actors like state, market, NGO and people. Keywords: drought management; impacts Water Nepal Vol. 12, No. 1&2, 2006 Page: 261-280